The contribution of neck dissection for residual neck disease after chemoradiotherapy in advanced oropharyngeal and hypopharyngeal squamous cell carcinoma patients - Suzuki, Masahiro; Kawakita, Daisuke; Hanai, Nobuhiro; Hirakawa, Hitoshi; Ozawa, Taijiro; Terada, Akihiro; Omori, Koichi; Hasegawa, Yasuhisa (International journal of clinical oncology, 2013)
Background Planned neck dissection after chemoradiotherapy (CRT) has remained controversial in advanced oro- and hypopharyngeal squamous cell carcinoma (OHSCC) patients. We evaluated the survival contribution of neck dissection (ND) in OHSCC patients with residual nodal disease following CRT. Methods We retrospectively evaluated 84 OHSCC patients with N2–3 disease treated at Aichi Cancer Center Hospital between 1995 and 2006. ND after CRT was performed for residual neck disease in 36 patients, but not in 48 patients to achieve a complete response. These two groups were analyzed in terms of both overall survival (OS) and regional control (RC), and surgical complications were evaluated. Results The 5-year OS was 76.7 % [95 % confidence interval (CI) 58.8–87.6] for the ND group and 73.9 % (58.6–84.3) for the non-ND group ( P = 0.883). The 5-year RC was 91.6 % (76.1–97.2) for the ND group and 81.1 % (65.4–90.2) for the non-ND group ( P = 0.252). Stratified by primary tumor site, the 5-year RC was 96.3 % (76.5–99.5) for the ND group, and 78.6 % (58.0–89.9) for the non-ND group ( P = 0.072) in oropharyngeal squamous cell carcinoma patients, and 77.8 % (36.5–93.9) for the ND group and 85.9 % (54.0–96.3) for the non-ND group ( P = 0.541) in hypopharyngeal squamous cell carcinoma patients. In addition, the complications after ND were tolerable. Conclusions We demonstrated that ND was feasible, safe, and correlated with clinical outcomes in OHSCC patients with residual nodal disease after CRT.